PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL CREATIVE PROBLEM SOLVING (CPS) BERBASIS KURIKULUM 2013 MATERI ARITMATIKA SOSIAL SMP/MTs - Zahera, Riska; Suanto, Elfis; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This study aims to produce mathematic learning device in the form of syllabus, lesson plan, and student worksheet based curriculum 2013 with Creative Problem Solving model on social arithmetic for junior high school. The study model used is ADDIE that consist of analyze, design, develop, implementation, and evaluation. Development process is done until the develop stage. The research instrument used is validity instrument and practicality instrument. Practicality instrument could not be implemented because of the school was closed. The validity instrument is a validation sheet to assess the feasibility of syllabus, lesson plans and student worksheet. Learning device developed are validated by three validators. Based on the data analysis, it can be conclude that the average value for syllabus is 87,40% in very valid category which means that syllabus is feasible to be used; as well as the average value for lesson plan and student worksheet are 83,33% and 81.31%. That are in valid category which means that lesson plan and student worksheet are feasible to be tested with improvement as the suggestion of the validators. Syllabus, lesson plan, and student worksheet are feasible to be used in the school after improvement as the suggestion of the validators.Key Words: Creative Problem Solving Learning Model, Learning Device, Social Arithmetic, and Validity.